Sistem Kekerabatan pada Praktik Politik di Desa Bungur (Kajian Sosiologi Politik) - Gultom, Teresiany Wulan (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2025)
Kinship relations can influence the system of government and political practices in each region which run in harmony with their respective functions. Each region has a leader who is elected through Regional Head Elections (Pilkada) as a form of democracy. In the implementation of democracy, people have the right to vote so that people's actions in choosing someone who is used as a figure or driving actor in society tend to put aside their rationality. This action can occur because there is still a kinship system. In the study of political sociology, kinship systems can develop and be maintained as a form of the diversity of social beings that basically can develop political evolution. This study aims to analyze the kinship system in political practice in Bungur Village and to determine the impact of this system so that this study uses the theory of solidarity by Emile Durkheim as an instrument in analyzing the phenomenon being studied. In this study the method used was a qualitative descriptive approach to describe the results of data collection which was carried out through interviews with several residents and using literature studies in providing references for writing articles. The results of the study show that kinship system can affect political practice and the running of the government system which should run according to its function, as well as this is not recommended to be implemented because it is included in the act of nepotism.